License to harass : law, hierarchy, and offensive public speech - Nielsen, Laura Beth (Cultural lives of law., 2004)
Offensive street speech--racist and sexist remarks that can make its targets feel both psychologically and physically threatened--is surprisingly common in our society. Many argue that this speech is so detestable that it should be banned under law. But is this an area covered by the First Amendment right to free speech? Or should it be banned?In this elegantly written book, Laura Beth Nielsen pursues the answers by probing the legal consciousness of ordinary citizens. Using a combination of field observations and in-depth, semistructured interviews, she surveys one hundred men and women, some.